(untitled) (Research, Society and Development, 2021)
The objective of this study is to analyze the scientific production on the use of films as a strategy in teaching bioethics. This is an integrative literature review, with retrieval of studies from the LILACS, BDENF, MEDILINE databases and the SciELO Virtual Library, through the DeCS / MeSH Bioethics, Teaching, Education, Nursing, Instructional Film and Video, Motion Pictures and the keywords Movies and Cinema. Eight studies were selected, uniformly distributed over the last 10 years, with text in English, Spanish and Portuguese, retrieved from the LILACS and MEDLINE databases, all classified at level of evidence IV. In this context, the studies rescued in this review point to positive results regarding the use of films in the teaching of bioethics, affirming the importance of incorporating this strategy in the pedagogical practices of health courses. There was widespread agreement on the use of this tool to discuss new or complex moral and philosophical ideas, which directly impact on clinical practice issues within the scope of health professionals. However, the literature emphasizes that this strategy should not be used as unpretentious and uncompromising entertainment.